Coronary artery involvement in pediatric Takayasu's arteritis: Case report and literature review - Mohan Shaun; Poff Sarah; Torok Kathryn S (BMC, 2013)
Abstract Takayasu's arteritis (TA) is a form of chronic vasculitis that typically occurs in young adult Asian females, but it can also present in younger patients not fitting this classic profile. In these cases, the sequelae are generally similar to those found in adults. The disease predominantly affects the aorta and its primary branches. However, the coronary arteries are also affected in up to 20% of cases, which may precipitate myocardial infarction. Imaging of the coronary arteries therefore becomes critically important in the evaluation of a patient with possible Takayasu's arteritis. We present a case of a pediatric patient with TA who had no symptoms of angina but who was found to have significant coronary artery involvement on diagnostic imaging. This necessitated tailoring of traditional management.